2020
DOI: 10.24200/sci.2020.55513.4258
|View full text |Cite
|
Sign up to set email alerts
|

A novel risk assessment approach using Monte Carlo simulation based on co-occurrence of risk factors: A case study of a petrochemical plant construction

Abstract: Nowadays, because of the advancement of technology and subsequently unpredictable events, it is important for addressing risk management as an important part of projects and business. In this paper, a novel approach based on Monte Carlo simulation has been proposed for risk assessment, which considers the co-occurrence of risks. In this method, the output of extended and classic Monte Carlo simulation is applied for co-occurrence-based risk assessment (CORA) and prioritization. Also, the magnitude in each sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…First, they listed the risks and then identified the relation among these risks using system dynamic approach. Their results showed that the risks such as inflation, cost, temperature, rain, and labor are the most important risks [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, they listed the risks and then identified the relation among these risks using system dynamic approach. Their results showed that the risks such as inflation, cost, temperature, rain, and labor are the most important risks [26].…”
Section: Literature Reviewmentioning
confidence: 99%